Connected but lonely: strategies to overcome fear of missing out and phubbing in the digital age / Muhammad Nabihan Abu Bakar and Masliya Yahya - Abu Bakar, Muhammad Nabihan; Yahya, Masliya (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In today’s digitally connected world, two behavioural phenomena that substantially impact our relationships with others and mental health are FoMO (Fear of Missing Out) and phubbing (phone snubbing). Both come from the pervasive influence of smartphones and social media, which have altered how we interact with one another and live in our society (Dempsey et al., 2019; Zhang, Li et al., 2020). Fear of missing out (FoMO) is one psychological phenomenon that may contribute to poor digital media use. FoMO refers to the pervasive apprehension that others may be having rewarding experiences while one is absent. Persons with a higher FoMO are assumed to have a greater desire to stay constantly up to date on what others are doing, such as through social media which can lead to problematic social media usage. Where as, phubbing is the behaviour of persons who are immersed in their phones and neglect the people and objects around them in social circumstances. This behaviour is common in the mobile internet era and can be seen in the home, work, and study settings.